open the brackets first
x and -x will get cancelled
take the LCM
1.) for the frst one multiply the denominator by x-3 andthe other one by x+3 and by taking lcm solve
2.) factorize the denominator of the frst one and take lcm of the two and solve
1) (x + 2/x + 3) - (x - 2/x -3)
= x + 2/x + 3 - x + 2/x +3
= 2/x +2/x +3
= 4/x + 3
2) (5x/x^2 - x - 6) - (2/x + 2)
=5/x - x - 6 - 2/x + 2
=7/x - x - 4
think this should be correct
I do not get the same answers as the other people did... To add or subtract fractions, you need to have a common denominator.
1) The common denominator is (x+3)(x-3). Convert both of your fractions so they have this denominator.